Seismic Failure Pattern Prediction in a Historical Masonry Minaret under Different Earthquakes - Halil Nohutcu (Advances in Civil Engineering)
Historical structures are the values that are of great importance to that country, showing the roots of a country, and must be passed on from generation to generation. This study attempts to make a contribution to this goal. Seismic damage pattern estimation in a historical brick masonry minaret under different ground motion levels is investigated by using updated finite element models based on ambient vibration data in this study. Imaret Mosque which was built in 1481 AD is selected for an application. Surveying measurement and material tests were conducted to obtain a 3D solid model and mechanical properties of the components of the minaret. Firstly, the initial 3D finite element model of the minaret was analyzed and numerical dynamic characteristics of the minaret were obtained. Then, ambient vibration tests as well as operational modal analysis were implemented in order to obtain the experimental dynamic characteristics of the minaret. The initial finite element model of the minaret was updated by using the experimental dynamic results. Lastly, linear and nonlinear time-history analyses of the updated finite element model of the minaret were carried out using the acceleration records of two different level earthquakes that occurred in Turkey, in Afyon-Dinar (1995) and Çay-Sultandağı (2002). A concrete damage plasticity model is considered in the nonlinear analyses. The conducted analyses indicate that the compressive and tension stress results of the linear analyses are not as realistic as the nonlinear analysis results. According to the nonlinear analysis, the Çay-Sultandağı earthquake would inflict limited damage on the minaret, whereas the Dinar earthquake would damage some parts of the elements in the transition segment of the minaret.